2016
DOI: 10.5812/ircmj.41931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Supplement on Prevention of PPROM and Improvement of some Pregnancy Outcomes in Pregnant Women with a History of PPROM: A Randomized Double -Blind Controlled Trial

Abstract: Background: Preterm premature rupture of membrane (PPROM) prior to 37 weeks' gestation is among the most common obstetrics problems, which is associated with prenatal mortality and several maternal and neonatal complications. History of PPROM is a risk factor for recurrence. Zinc has an important effect on the strength of membranes by affecting collagen [tensile] strength -a substance with immunity mechanism and antioxidant properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Another study found that plasma zinc concentrations in women with PPROM were significantly lower than in controls, lending credence to our findings (27). On the contrary, it was discovered in a study looking into the effect of zinc supplementation in preventing PPROM that zinc sulfate intake had no effect on PPROM prevention (28). Similarly, researchers discovered that zinc supplementation had no effect on the incidence of PPROM in a study of 196 women who were 19-20 weeks pregnant (29).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that plasma zinc concentrations in women with PPROM were significantly lower than in controls, lending credence to our findings (27). On the contrary, it was discovered in a study looking into the effect of zinc supplementation in preventing PPROM that zinc sulfate intake had no effect on PPROM prevention (28). Similarly, researchers discovered that zinc supplementation had no effect on the incidence of PPROM in a study of 196 women who were 19-20 weeks pregnant (29).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 40 mg daily zinc sulfate supplementation prevented the risk of preterm prelabor rupture of membranes during the mid‐ and late trimesters in pregnant women 165 . Interestingly, this trace mineral is considered an alternative to many of the antibiotics that are used for the treatment of diarrhea in newborn calves 166,167 . It plays vital roles in synthesizing humoral immunity and IgG in mammary tissue, and is secreted in colostrum and taken in by newborn calves 168,169 .…”
Section: Factors Affecting On Maternal Immune Responsementioning
confidence: 99%
“…165 Interestingly, this trace mineral is considered an alternative to many of the antibiotics that are used for the treatment of diarrhea in newborn calves. 166,167 It plays vital roles in synthesizing humoral immunity and IgG in mammary tissue, and is secreted in colostrum and taken in by newborn calves. 168,169 Dairy cows receiving higher zinc in their feed have higher production of immunoglobulins and improved passive immunity in their calves.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…Furthermore, that disruption of collagen occurs as a result of the effects of zinc-dependent matrix metalloproteinase and tissue-specific inhibitors. The effect of supplementation (daily 40 mg zinc sulphate) vs. placebo treatment to prevent PPROM during the second and early third trimesters in pregnant women who had previously been affected was conducted by Shahnazi et al [52] among women attending an Iranian midwifery clinic. Unfortunately, the researchers were unable to demonstrate any superiority of zinc supplementation on the prevention of PPROM and improvement of gestational age at birth or any anthropometric measurements.…”
Section: Zincmentioning
confidence: 99%